GOLD POTENTIAL OF THE UPPER DEVONIAN BASAL CONGLOMERATES OF THE KANIN PENINSULA (NENETS AUTONOMOUS DISTRICT, RUSSIA) - M.A. Pavlova; D.A. Varlamov; S.M. Snigirevsky; D.V. Zarkhidze; S.V. Petrov; M.A. Rassomakhin (Минералогия, 2022)
Native gold and garnets are described for the first time in heavy concentrates from coarse-grained sediments of the Upper Devonian Tayaokuyakha Formation, which occurs on the eroded Upper Riphean schists with angular and azimuthal unconformity (middle reaches of the Murseyakha River, Kanin Peninsula, Nenets autonomous district, Russia). Particular attention was paid to indicators of primary source of native gold for the Upper Devonian conglomerates. The composition of weakly rounded almandine-spessartine garnets indicates their metamorphic origin and allows us to relate the primary source of native gold in conglomerates (D3tk) with underlying metamorphosed Riphean strata or intrusive rocks in them. Native gold is mainly characterized by a heterogeneous composition and contains Ag, Cu and Hg. The poorly rounded native gold grains, the absence of supergene rims and preservation of mineral inclusions in the margins indicate its proximal primary source. The presence of Cu suggests a link of native gold with mafic/ultramafic rocks: metamorphosed dikes of dolerites of the Nekhaiteyakha metagabbroid complex (mνβRF3) or dolerite dikes of the Kanin-Timan complex (βD3kt), which intrude the Precambrian metamorphic schists. It is established that the Devonian conglomerates are intermediate reservoirs for the possible present-day placer formation.